Development of a 3D Animal Miniature Learning Media Based on Augmented Reality Using Web Edu Assembler to Improve Elementary School Students’ Science Learning Outcomes - Lulu Aulia Karimah; Sudi Dul Aji; Arnelia Dwi Yasa (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
Science learning in elementary schools still faces challenges in presenting abstract concepts, including metamorphosis, which often makes it difficult for students to understand the stages of animal transformation comprehensively. This study aims to develop and evaluate the feasibility, practicality, and effectiveness of a 3D animal miniature learning media based on Augmented Reality (AR) using Web Edu Assembler for the topic of complete and incomplete metamorphosis for third-grade elementary students. The study employed a Research and Development method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The effectiveness test was conducted using a one-group pretest–posttest design involving 55 third-grade students. The results indicate that the developed media is highly feasible based on expert validation from material experts (96.4%), media experts (98%), and language experts (100%). The media was also considered highly practical based on teacher assessments and student responses. The average pretest score of 52.20 increased to 93.09 in the posttest, with an N-Gain score of 0.8250, categorized as high.